Christening pagan mysteries : Erasmus in pursuit of wisdom - Boyle, Marjorie O'Rourke, 1943- (Erasmus studies, 1981)
This is the first book devoted to investigating the scholarly commonplace that Erasmus' revival of classical learning defines his evangelical humanism.